2018
DOI: 10.1016/j.cyto.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute infection with Strongyloides venezuelensis increases intestine production IL-10, reduces Th1/Th2/Th17 induction in colon and attenuates Dextran Sulfate Sodium-induced colitis in BALB/c mice

Abstract: Helminth infection can reduce the severity of inflammatory bowel disease. However, the modulatory mechanisms elicited by helminth infection are not yet fully understood and vary depending on the experimental model. Herein we evaluated the effect of acute infection of BALB/c mice with Strongyloides venezuelensis on the clinical course of ulcerative colitis induced by Dextran Sulfate Sodium (DSS) treatment of these animals. For the experiments, S. venezuelensis-infected BALB/c mice were treated orally with 4% DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…For clinical score evaluation, eight sex-and age-matched animals per experimental group were weighted, appearance and stool samples were checked manually. Clinical score was applied as described by Van der Sluis et al 45 and by Rodrigues et al 90 with modifications. Each parameter was scored as follows:…”
Section: Discussionmentioning
confidence: 99%
“…For clinical score evaluation, eight sex-and age-matched animals per experimental group were weighted, appearance and stool samples were checked manually. Clinical score was applied as described by Van der Sluis et al 45 and by Rodrigues et al 90 with modifications. Each parameter was scored as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that while the presence of parasite eggs in the feces could be one of the factors that alter the fecal microbiota, other factors are likely to be more important, such as the host immune response or parasite-secreted products. S. venezuelensis infection induces T-helper type 1 (Th1) and Th2 immune responses in the host duodenum and colon (Rodrigues et al, 2018), with Th2 responses in particular causing changes to the intestinal physiology, including increased mucosal permeability, enhanced smooth muscle contractility, and an altered microbiota (Zhao et al, 2003; Artis and Grencis, 2008; Farid et al, 2008; Su et al, 2011). In the present study, we found that Th2-related genes were upregulated in the middle phase of infection.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10's protective function has been identified in many colitis models, including the DSS-induced colitis model and the CD45RB hi T cell transfer colitis model, which mimic ulcerative colitis (UC) and Crohn's disease, respectively ( 66 ). IL-10 inhibits IFN-γ production by Th1 cells in mice reconstituted with CD45RB hi CD4 + T cells ( 67 ) and reduces Th17 responses in the DSS model ( 68 , 69 ). As microbiota is involved in the normal physiological status of the colon ( 70 ), the immunomodulatory effects of microbiota-produced short-chain fatty acids (SCFAs) have been examined.…”
Section: Il-10 and Il-22 In Mucosal Inflammationmentioning
confidence: 99%